(untitled) (International Journal of Physiotherapy, 2016)
Background: Lately, childhood obesity has gained more attention. The present study constructed to compare the effectiveness of aerobic interval exercises and dietary control on plasma adipokines level, lipid profile and the health-related quality of life in overweight or obese children. Methods: Thirty-seven overweight or obese children at the age from 10-18 years were recruited and randomly classified into aerobic interval exercises (AIE) and dietary control (DC) groups. The Training load for AIE group was eight weeks of an intermittent short high intense burst of exercises throughout a regular training program primarily consisted of treadmill training. Whereas, subjects in the DC group were engaged in a balanced dietary plan. Plasma adipokines, lipid profile, and the health-related quality of life were assessed before and after the intervention. Results: Both groups were similar at the baseline (p>0.05). Within the AIE group; leptin, adiponectin and all lipid profile measures significantly changed (p<0.05). But, within the DC group, only leptin, high-density lipoprotein cholesterol (HDL-Cho) and low-density lipoprotein cholesterol (LDL-Cho) levels have been significantly changed (p<0.05). Further, the health-related quality of life (HRQL) indicated significant differences within both groups (p<0.05) with regard to both physical and psychosocial health. Finally, significant differences of leptin, HDL-Cho, LDL-Cho levels and the psychosocial health (p<0.05) were recorded between both groups in favor of the AIE group. Conclusion: However, both aerobic interval training and balanced dietary controlare useful to improve plasma adipokines level, lipid profile, and the HRQL in overweight or obese children. But, aerobic interval training is more helpful.